Hyperelastic mechanical properties of chopped aramid fiber-reinforced rubber composite under finite strain. (1st July 2020) - Gao, Jianhong; Yang, Xiaoxiang; Guo, Jinquan; Huang, Jianren
Abstract: Chopped aramid fiber-reinforced rubber composite (AFRC) has been widely used in the construction industry owing to its excellent characteristics; however, the study of the mechanisms that give rise to its properties remains a challenge because of the hyperelastic properties of the rubber matrix, coupled with the large aspect ratio and anisotropy of the aramid fibers. This study aimed to investigate the hyperelastic mechanical properties of AFRC by combining experimental methods and numerical prediction. In this research, a finite element model was thoroughly verified using strain energy analysis. The hyperelastic behavior of AFRC was studied using a three-dimensional numerical method based on the proposed representative volume elements, and a good agreement between the experimental and numerical results was demonstrated. In addition, the stretched ratio was studied which would be considered as a reference for the study of internal mechanism of AFRCs.